2007
DOI: 10.1093/njaf/24.4.276
|View full text |Cite
|
Sign up to set email alerts
|

Surface Compaction Estimates and Soil Sensitivity in Aspen Stands of the Great Lakes States

Abstract: Aspen forests in the Great Lakes States support much of the regional timber industry. Management-induced soil compaction is a concern because it affects forest health and productivity and soil erosion. Soil compaction increases bulk density and soil strength and can also decrease air and water movement into and through the soil profile. Currently, most inventories, and specifically the Forest Inventory and Analysis program, use qualitative estimates of soil compaction. This study compared qualitative estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…An interesting finding was the differences in response to soil compaction treatments among sites, where effects (depth, magnitude, and duration) were most pronounced at the Huron site, intermediate at Chippewa, and not apparent at Ottawa. These effects are generally opposite of common perceptions related to soil texture and susceptibility to compaction (Steber et al 2007. Stone (2001 reported that operating conditions during pre-treatment harvesting at the Chippewa and Ottawa sites were less than ideal, with unfrozen soil or discontinuous frost present at these locations.…”
Section: Compaction Effects On Soil Bulk Densitymentioning
confidence: 96%
“…An interesting finding was the differences in response to soil compaction treatments among sites, where effects (depth, magnitude, and duration) were most pronounced at the Huron site, intermediate at Chippewa, and not apparent at Ottawa. These effects are generally opposite of common perceptions related to soil texture and susceptibility to compaction (Steber et al 2007. Stone (2001 reported that operating conditions during pre-treatment harvesting at the Chippewa and Ottawa sites were less than ideal, with unfrozen soil or discontinuous frost present at these locations.…”
Section: Compaction Effects On Soil Bulk Densitymentioning
confidence: 96%
“…However, in dry years, the higher water‐holding capacity in the wheel tracks may be beneficial for seedlings, as long as the soil is not too compacted for root penetration. Steber et al (2007) found that high‐porosity soils often show improved root–soil contact, water holding capacity, thermal regimes and/or nutrient uptake after compaction, if the forest floor cover is also removed. The mean porosity of the upper 0 to 5 cm of the mineral soil at Site R was 0.59 m 3 m −3 in the undisturbed areas (Hansson et al, 2018a), and moderate soil compaction at this site may have been beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…The same technique was successfully applied by Lafuerza et al (2005), Choi and Kim (2006), Sarti et al (2012), and Styllas (2014), proving to be useful for the high-resolution sequence stratigraphic analysis and three-dimensional reconstruction of alluvial to coastal successions. This tool has been used for reliable assessment of the effects of compaction on soil productivity (Steber et al, 2007), to estimate threshold friction velocity of wind erosion in the field (Li et al, 2010), and for stratigraphic and geotechnical investigations (Brideau et al, 2011). Pocket penetrometer may provide almost continuous record of in situ properties of soils.…”
Section: Introductionmentioning
confidence: 99%
“…Pocket penetrometer may provide almost continuous record of in situ properties of soils. This tool has been used for reliable assessment of the effects of compaction on soil productivity (Steber et al, 2007), to estimate threshold friction velocity of wind erosion in the field (Li et al, 2010), and for stratigraphic and geotechnical investigations (Brideau et al, 2011).…”
Section: Introductionmentioning
confidence: 99%